The State Council years, 1936-1942 : speeches made in the legislature compiled under the auspices of the Philip Gunawardena Commemoration Society - Guṇavardhana, Pilip; Meegama, Ananda; Philip Gunawardena Commemoration Society (Colombo : Godage International Publishers, 2006)
Includes a brief biography of Philip Gunawardena.
Keywords: Sri Lanka -- Politics and government -- 20th century